Sex Differences in Autism Spectrum Disorder: Focus on High Functioning Children and Adolescents - de Giambattista, Concetta; Ventura, Patrizia; Trerotoli, Paolo; Margari, Francesco; Margari, Lucia (Frontiers in Psychiatry, 2021)
Autism Spectrum Disorder (ASD) has historically been studied, known and diagnosed in males. Females tend to remain unidentified, especially those with average intelligence abilities. This sex/gender difference might be partially explained by biological risk factors, but it is probably also bound to methodological issues. The present study aims to examine phenotypic characteristics (cognitive, emotive, socio-communicative and academic) of a group of 54 females with ASD matched to a group of 55 males with ASD (3-18 years), all without cognitive impairment. Results suggest that there are subtle, yet potentially meaningful, quantitative and qualitative phenotypic differences between females and males that common screening tests are not always sensitive enough to recognize. Further studies to improve practice and course for the assessment of females, reducing sex/gender-based inequities in ASD care, are required.